Deciphering distinct genetic risk factors for FTLD-TDP pathological subtypes via whole-genome sequencing - Cyril Pottier; Fahri Küçükali; Matt Baker; Anthony Batzler; Gregory D. Jenkins; Marka van Blitterswijk; Cristina T. Vicente; Wouter De Coster; Sarah Wynants; Pieter Van de Walle; Owen A. Ross; Melissa E. Murray; et al. (Nature Communications)
Abstract Frontotemporal lobar degeneration with neuronal inclusions of the TAR DNA-binding protein 43 (FTLD-TDP) is a fatal neurodegenerative disorder with only a limited number of risk loci identified. We report our comprehensive genome-wide association study as part of the International FTLD-TDP Whole-Genome Sequencing Consortium, including 985 patients and 3,153 controls compiled from 26 institutions/brain banks in North America, Europe and Australia, and meta-analysis with the Dementia-seq cohort. We confirm UNC13A as the strongest overall FTLD-TDP risk factor and identify TNIP1 as a novel FTLD-TDP risk factor. In subgroup analyzes, we further identify genome-wide significant loci specific to each of the three main FTLD-TDP pathological subtypes (A, B and C), as well as enrichment of risk loci in distinct tissues, brain regions, and neuronal subtypes, suggesting distinct disease aetiologies in each of the subtypes. Rare variant analysis confirmed TBK1 and identified C3AR1, SMG8, VIPR1, RBPJL, L3MBTL1 and ANO9, as novel subtype-specific FTLD-TDP risk genes, further highlighting the role of innate and adaptive immunity and notch signaling pathway in FTLD-TDP, with potential diagnostic and novel therapeutic implications.